Influence of mineral fertilizers on fertility of sod-podzolic soil, productivity and quality of grain crops - I. V. Lyskova (Аграрная наука Евро-Северо-Востока)
Experiments were conducted in 2008.2015 in Kirov region. Effectiveness of liming, input of nitric (N90 kg/ha of acting matter) and increasing dozes of phosphoric fertilizers (50, 100, 150, and 200 kg/ha of acting matter) in complex with nitric-potassium fertilizers (90 kg/ha of acting matter each) on agronomical parameters of soil, productivity and grain quality of winter rye, spring wheat and oat was studied on stationary field experiment. In variant without liming and fertilizing significant acidification of soil was taken place (pH 3.9, Al 9.5 mg/100 g of soil) in compare with initial values (pH 4.5...4.7). Inputting N90P100-200K90 leads to increase in exchangeable and hydrolytic acidity, content of mobile aluminum (up to 13.6.15.4 mg/100 g, and phosphorus (up to 156.209 mg/kg on non-liming and 147.248 mg/kg on liming backgrounds at phosphorus concentration in soil solution 0.56.0.68 and 0.75.1.39 mg/l correspondingly). On the liming-free background, productivity of winter rye was in average 1.92, oat - 3.90, and wheat - 2.26 t/ha; liming increased productivity on 15.27, 13.29, and 16.32% correspondingly. Nitric fertilizers had significant influence in forming of addition yield. In variant N90 on the liming background 1.15 t/ha of winter rye grain, 1.6 t/ha of oat, and 0.78 t/ ha of wheat was gathered additionally and the highest recoupment of fertilezers with grain (12.6, 17.8, and 8.7 kg) was reached. Maximal levels in productivity of cereals obtained in variants with NPK input; tendency to increase in productivity because of increasing dozes of super-phosphate is marked on liming-free background. Nitric fertilizers significantly influenced on content of nitrogen, raw protein and gluten in spring wheat grain; correlation is marked between spring wheat productivity and content of raw protein (r = 0.79) and gluten (r = 0.78) in grain. Test weight of all crops was higher then basic norm independent on fertilizers input.